Global stabilization of stochastic nonlinear systems - Bensoubaya, M.; Ferfera, A.; Iggidr, A. (Proceedings of the 37th IEEE Conference on Decision and Control (Cat. No.98CH36171), 1998)
We consider stochastic nonaffine nonlinear control systems dx/sub t/=f(x/sub t/,u) dt+g(xt,u) d/spl omega//sub t/, /spl omega/ being a standard Wiener process, for which we give a sufficient condition for global stabilization by a bounded smooth state feedback which is explicitly given. This condition generalizes the well known Jurdjevic-Quinn result (1978) for deterministic affine control systems.